Isbat Nikah Sebagai Solusi Penolakan Calon Pengantin Perempuan Tanpa Kejelasan Nasab di Pengadilan Agama Pacitan - Moch Mu'ti; Rohmah Maulidia; Luhur Prasetiyo (Journal of Economics, Law, and Humanities, 2024)
Case of community rejection of a prospective son-in-law whose lineage is unclear. According to the community, the rejection was based on the seeds, burdens, and unequal weight of the prospective partner in Pacitan. This is what underlies how to find a solution to resolve society's rejection of prospective daughters-in-law who do not have a clear lineage through marriage isbat at the Pacitan Religious Court. This field research using qualitative methods aims to describe how and what the reasons and legal implications of the rejection of women whose fate is unclear are. The results of the research showed that the reason parents rejected their prospective daughter-in-law was because they did not have a clear lineage. This is based on the Javanese law, which is still adhered to regarding selecting prospective marriage partners: seed, bebet, and weight. Still, this problem can be resolved through marriage isbat at the Pacitan Religious Court to change the status on the birth certificate and family card.